(untitled) (Journal of Dissability Studies and Research (JDSR), 2023)
The paradigm shift in understanding disability needs to be carried out in line with the spirit of reform and democracy which is based on strengthening the basic principles of human rights. The writing of this article uses literature and document studies. Paradigm in handling or providing services for persons with disabilities. Current research shows a close relationship between the public paradigm of disability and persons with disabilities and discriminatory behavior experienced by persons with disabilities in their daily lives. The general understanding of people in the world, including Indonesia, about persons with disabilities still tends to be negative. This negative understanding is because society generally defines and treats persons with disabilities based on a mindset that is dominated by the concept of normality which has implications for stigmatization and discrimination against persons with disabilities. This is due to the limited dissemination of information and official education from the government or related authorities and the lack of socialization of the results of scientific studies on disability and persons with disabilities. This article aims to describe a literature review related to the understanding of disability and persons with disabilities. It is hoped that this study can contribute to overcoming the gap in information and education about disability and persons with disabilities, as well as providing proper understanding and better behavior in respecting the human rights of persons with disabilities in Indonesia. With the right understanding and behavior, it is hoped that the community will contribute to the protection and social welfare of persons with disabilities in Indonesia in line with the spirit of reform and democracy.